AN INTEGRATED RISK INFORMED DECISION MAKING IN THE NUCLEAR INDUSTRY - Borysiewicz, Mieczysław Józef; Kowal, Karol; Prysiński, Piotr; Dąbrowski, Marcin (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2013)
The regulatory body, established to ensure safety of nuclear facilities, is expected to make right decisions and provide appropriate regulations for the nuclear industry. The traditional manner of its activity has been based on a deterministic approach to safety analyses. However, increased maturity of Probabilistic Safety Assessment (PSA) makes it complementary to deterministic studies. The new IAEA concept, described in this article, is to apply an integrated approach by combining both deterministic and probabilistic insights with other requirements affecting the decision making process.